Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1242/jcs.01606
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 and PARP-2 interact with nucleophosmin/B23 and accumulate in transcriptionally active nucleoli

Abstract: The DNA damage-dependent poly(ADP-ribose) polymerases-1 and -2 (PARP-1 and PARP-2) are survival factors that share overlapping functions in the detection, signaling and repair of DNA strand breaks resulting from genotoxic lesions in mammalian cells. Here we show that PARP-1 and PARP-2 subnuclear distributions partially overlap, with both proteins accumulating within the nucleolus independently of each other. PARP-2 is enriched within the whole nucleolus and partially colocalizes with the nucleolar factor nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
159
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 52 publications
16
159
2
Order By: Relevance
“…It has been suggested that PARP-1 and -2 have to act as heterodimers in BER; thus, the absence of one of each would have the same consequence on repair efficiency (Schreiber et al, 2002). However, recent results show that nuclear colocalization of PARP-1 and -2 is low outside the nucleolus, even on stimulation with DNA-damaging agents, supporting the hypothesis that PARP-1 and -2 might have distinct targets and that their heterodimerization might be restricted to the nucleolus (Meder et al, 2005). A double-knockout mouse is not available since the deletion of both PARP-1 and -2 is embryonically lethal (Ménissier de Murcia et al, 2003), but it would be interesting to determine whether our observation can be confirmed by a lack of additional protection in PARP-1 À/À or -2 À/À mice treated with a PARP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that PARP-1 and -2 have to act as heterodimers in BER; thus, the absence of one of each would have the same consequence on repair efficiency (Schreiber et al, 2002). However, recent results show that nuclear colocalization of PARP-1 and -2 is low outside the nucleolus, even on stimulation with DNA-damaging agents, supporting the hypothesis that PARP-1 and -2 might have distinct targets and that their heterodimerization might be restricted to the nucleolus (Meder et al, 2005). A double-knockout mouse is not available since the deletion of both PARP-1 and -2 is embryonically lethal (Ménissier de Murcia et al, 2003), but it would be interesting to determine whether our observation can be confirmed by a lack of additional protection in PARP-1 À/À or -2 À/À mice treated with a PARP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…All images from a single experiment were handled identically. Where indicated, mouse monoclonal anti-C-II-10 anti-PARP1 antibody and Alex Fluor-488-conjugated goat anti-mouse IgG were added to allow simultaneous visualization of PARP1 (76,77) and pADPr.…”
Section: Methodsmentioning
confidence: 99%
“…PARP-2 protein can be divided into similar functional regions as PARP-1: The Nterminus of mouse PARP-2 contains the DNA binding domain (DBD), followed by domain E and the catalytic domain (domain F) [8]. The DBD is formed by a SAP domain that is responsible for DNA binding [20], and contains a functional nuclear localization signal (NLS) [21] and a nucleolar localization signal (NoLS) [22]. A caspase-3 cleavage site defines the border between the DBD and domain E, which is homologous to the caspase-3 site in the E domain of PARP-1 [23].…”
Section: The Parp Superfamilymentioning
confidence: 99%
“…PARP-2 interacts with topoisomerase I and topoismerase II [40,55] and may thus regulate the rearrangement of DNA structure in conjunction with RNA transcription. Moreover, PARP-2 has been shown to interact with nucleophosmin/B23 [22] that is involved in rRNA transcription [70]. RNA polymerase I inhibition removes PARP-2 from the nucleolus, however the deletion of PARP-2 does not change rRNA expression.…”
Section: Parp-2 In the Regulation Of Gene Expressionmentioning
confidence: 99%